2008
DOI: 10.1074/jbc.r800042200
|View full text |Cite
|
Sign up to set email alerts
|

The Gregarious Lipid Droplet

Abstract: Cytoplasmic lipid droplets were considered until recently to be in the same category as glycogen granules, simple storage sites for energy, waxing and waning as metabolic energy needs dictated, but otherwise inert particles. It has become clear, however, that droplets are much more than isolated storage depots in the cell and that they can skate around on the cytoskeleton, physically interact with several organelles over short or long durations, and be beasts of burden, storing important molecules unrelated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
214
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(228 citation statements)
references
References 56 publications
8
214
0
6
Order By: Relevance
“…Recently, LDs have been redefined as authentic organelles that are actively engaged in multiple functions, and these have been reviewed in many recent articles (Murphy 2001;Martin et al 2006;Ducharme et al 2008;Fujimoto et al 2008;Goodman 2008;Olofsson et al 2008;Thiele et al 2008;Murphy et al 2009;Walther et al 2009;Beller et al 2010). The name, lipid droplets, implies the opposite: a static and inert nature.…”
mentioning
confidence: 99%
“…Recently, LDs have been redefined as authentic organelles that are actively engaged in multiple functions, and these have been reviewed in many recent articles (Murphy 2001;Martin et al 2006;Ducharme et al 2008;Fujimoto et al 2008;Goodman 2008;Olofsson et al 2008;Thiele et al 2008;Murphy et al 2009;Walther et al 2009;Beller et al 2010). The name, lipid droplets, implies the opposite: a static and inert nature.…”
mentioning
confidence: 99%
“…The one-cell-layer gametophyte could be observed easily with confocal microscopy for the subcellular OBs and other structures. Transient expression of various gene constructs transformed into gametophyte cells revealed that all OBs were linked to the endoplasmic reticulum (ER), that oleosins were synthesized in extended regions of the ER, and that two different oleosins were colocated in all OBs.Eukaryotes and prokaryotes contain neutral lipids in subcellular droplets as food reserves and/or for other purposes (Hsieh and Huang, 2004;Martin and Parton, 2006;Goodman, 2008;Rajakumari et al, 2008). These lipid droplets are present in seeds, pollens, fruits, and flowers of higher plants; the vegetative and reproductive organs of lower plants, algae, fungi, and nematodes; mammalian organs/tissues, such as mammalian glands and adipose tissues; and bacteria.…”
mentioning
confidence: 99%
“…Longtemps désignée sous le nom PAT -qui désignait les trois principaux membres de cette famille : la périlipine, l'adipophiline (ou ADRP, adipose differentiation-related protein) et Tip47 (tail interacting protein of 47 kDa) [8] -, cette famille a été récemment rebaptisée PLIN, pour périlipine [9]. Chacune de ces protéines a des caractéristiques qui lui sont propres, comme leur distribution tissulaire, mais aussi et surtout leur rôle dans la régulation du contenu des gouttelettes lipidiques [10]. Elles sont échangeables à la surface des gouttelettes pour répondre à certains besoins de la cellule [11,12].…”
Section: Structure Et Composition Des Gouttelettes Lipidiquesunclassified
“…Ainsi, dans des conditions nécessitant l'hydrolyse rapide des acides gras estérifiés pour générer des acides gras libres, la monocouche entourant une gouttelette doit rapidement se réduire. Sa continuité avec le réticulum permettrait de comprendre comment les phospholipides de cette monocouche peuvent être rapidement réintégrés dans le feuillet externe de la bicouche de phospholipides du réticulum [10]. À l'inverse, certaines études ont suggéré que les gouttelettes pourraient se détacher complètement du réticulum et migrer, à l'instar d'un trafic vésiculaire, pour fusionner avec d'autres domaines du réticulum ou d'autres organites [23].…”
Section: Formation Des Gouttelettes Lipidiquesunclassified